Vulnerability to recurrent episodes of acute decompensation/acute-on-chronic liver failure characterizes those triggered by indeterminate precipitants in patients with liver cirrhosis. - Hitomi Hoshi; Po-Sung Chu; Aya Yoshida; Nobuhito Taniki; Rei Morikawa; Karin Yamataka; Fumie Noguchi; Ryosuke Kasuga; Takaya Tabuchi; Hirotoshi Ebinuma; Hidetsugu Saito; Takanori Kanai; et al. (PLoS ONE)
Background Acute decompensation (AD) of liver cirrhosis (LC) and subsequent acute-on-chronic liver failure (ACLF) are fatal and impair quality of life. Insufficient knowledge of the highly heterogeneous natural history of LC, including decompensation, re-compensation, and possible recurrent decompensation, hinders the development and application of novel therapeutics. Approximately 10%-50% of AD/ACLF is reported to be precipitated by any indeterminate (unidentifiable, cryptogenic, or unknown) acute insults; however, its clinical characteristics are unclear. Methods We conducted a single-center observational study of 2165 consecutively admitted patients with LC from January 2012 to December 2019. A total of 466 episodes of AD/ACLF in 285 patients, including their 285 first indexed AD/ACLF, were extracted for analysis. Stratified analyses of different acute precipitants, classified as indeterminate (AD/ACLFIND), bacterial infection (AD/ACLFBAC), gastrointestinal bleeding, active alcoholism, and miscellaneous, were performed. Results AD/ACLFIND was the leading acute precipitant (28%), followed by AD/ACLFBAC (23%). AD/ACLFIND showed better survival outcomes than AD/ACLFBAC (P = 0.03); however, hyperbilirubinemia, hyponatremia, or leukocytosis significantly and uniquely characterized subgroups of AD/ACLFIND with comparable or even worse survival outcomes than those of AD/ACLFBAC. Patients with subsequent AD/ACLF significantly tended to suffer from AD/ACLF with any organ failure in AD/ACLFIND but not in AD/ACLFBAC (P = 0.004, for trend). In competing risk analysis, patients with AD/ACLFIND were significantly more vulnerable to suffer from recurrent episodes of AD/ACLF within 180 days, compared to those triggered by other precipitants (P = 0.04). Conclusions AD/ACLFIND, the leading acute precipitant, also plays a role in subsequent AD/ACLF. An abruptly exacerbating, remitting, and relapsing nature of systemic inflammation underlying AD/ACLF may also be useful for risk estimation.